The Results of Liver Transplantation in Turkey - Mehmet HABERAL; Hasan TELATAR; Nebil BÜYÜKPAMUKÇU; Halis ŞİMŞEK and Burhan KAYHAN and Gülnaz ARSLAN and Nevzat BİLGİN and Enver EKİCİ and Bedri UZUNALİMOĞLU and Aytekin BESİM and et (Turkish Journal of Gastroenterology, 2020)
-